2019
DOI: 10.18512/1980-6477/rbms.v18n2p178-191
|View full text |Cite
|
Sign up to set email alerts
|

Densidade De Plantas E Adubação Nitrogenada Em Cobertura No Desenvolvimento E Desempenho Produtivo Do Milho

Abstract: Alterações no arranjo de plantas na cultura do milho permitem maiores populações e exigem adequações nas doses de nitrogênio fornecidas. Objetivou-se avaliar o efeito de doses de nitrogênio em cobertura no desenvolvimento e desempenho produtivo do milho de segunda safra em diferentes densidades de plantas. O experimento foi conduzido em duas safras com o híbrido AG9010 YG, em blocos casualizados e parcelas subdivididas, com quatro repetições. Nas parcelas, alocaram-se as populações de plantas (40, 60, 80 e 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Only the plant population factor had a significant effect (P < 0.05) on all studied variables, except for the plant height characteristic (Table 1). With the increase in the population of 35,000 to 80,000 plants ha -1 the stem diameter linearly decreased (Figure 2a), agreeing with the works of Brachtvogel et al (2012) and Zucareli et al (2019), who also observed a decrease in stem diameter with increasing populations of 30, 45, 60, 75, 90 and 105; 40, 60, 80 and 100 thousand plants ha -1 , respectively. Plants when subjected to high populations due to intraspecific competition, seek growth above the canopy to avoid shading and capture sunlight, thus the photoassimilates are intended to promote accelerated growth, thus reducing other parts of the plant such as the stem diameter (TAIZ, ZEIGER, 2017).…”
Section: Morphophysiological Characterization Of Different Plant Popu...supporting
confidence: 88%
“…Only the plant population factor had a significant effect (P < 0.05) on all studied variables, except for the plant height characteristic (Table 1). With the increase in the population of 35,000 to 80,000 plants ha -1 the stem diameter linearly decreased (Figure 2a), agreeing with the works of Brachtvogel et al (2012) and Zucareli et al (2019), who also observed a decrease in stem diameter with increasing populations of 30, 45, 60, 75, 90 and 105; 40, 60, 80 and 100 thousand plants ha -1 , respectively. Plants when subjected to high populations due to intraspecific competition, seek growth above the canopy to avoid shading and capture sunlight, thus the photoassimilates are intended to promote accelerated growth, thus reducing other parts of the plant such as the stem diameter (TAIZ, ZEIGER, 2017).…”
Section: Morphophysiological Characterization Of Different Plant Popu...supporting
confidence: 88%
“…Nutritional management is important for the corn crop to express its maximum production potential (ZUCARELI et al, 2019). However, in saline environments the ionic interactions that affect the availability, absorption and transport of nutrients are even more complex, mainly due to differences in concentration and ionic composition (higher accumulation of Na + and Cl -), resulting in lower absorption and concentrations of N, P, K, Ca and Mg (SOUSA et al, 2010;IBRAHIM et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Macronutrients and especially N adequacy in plants are the factors that can make a difference in their production and tackle the problem of food demand when used cautiously [2,3]. N fertilization for maize cultivation can be very crucial to provide a good development and growth of maize plants [4]. Nitrogen uptake efficacy in fully cultivated soils has always been a difficult task in farming because the N flow in an ecosystem can vary from runoff to surface waters to N atmospheric release [5][6][7].…”
Section: Introductionmentioning
confidence: 99%